Standard three-dimensional glomeruli of the Manduca sexta antennal lobe: a tool to study both developmental and adult neuronal plasticity. - Huetteroth, W; Schachtner, J (2005)
The metamorphosing antennal lobe (AL) of the sphinx moth Manduca sexta serves as an established model system for studying neuronal development. To improve our understanding of mechanisms involved in neuronal plasticity, we have analyzed the size, shape, and localization of ten identified glomeruli at three different time points during development and in the adult, viz., (1) 13 days after pupal eclosion (P13), which reflects a time when the basic glomerular map has formed, (2) immediately after adult eclosion (A0), which represents a time when the newly formed glomeruli are uninfluenced by external odors, and (3) 4 days after adult eclosion (A4), which reflects a time when the animals have been exposed to surrounding odors. Our data from normally developing ALs of male M. sexta from P13 to A0 revealed an increase in size of all examined glomeruli of between 40% and 130%, with the strongest increases occurring in two of the three sex-specific glomeruli (cumulus, toroid). From A0 to A4, the cumulus and toroid increased significantly when correlated to AL volume, whereas the other glomeruli reached the sizes gained after A0. This study was based on antibody staining against the ubiquitous synaptic vesicle protein synaptotagmin, confocal laser scan microscopy, and the three-dimensional (3D) analysis tool AMIRA. Tissue permeability and therefore reliability of the staining quality was enhanced by using formalin/methanol fixation. The standard 3D glomeruli introduced in this study can now be used as basic tools for further examination of neuronal plasticity at the level of the identified neuropil structures, viz., the glomeruli of the AL of M. sexta.